Global food security portal - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
The global Food Security Portal, facilitated by the International Food Policy Research Institute (IFPRI), presents up-to-date data and information about dynamic developments in the world food system and increases policymakers’ ability to respond quickly and adequately.